Evaluation, characterization and confirmation of hybrids derived from diverse CMS sources in sunflower (Helianthus annuus L.): Evaluation, characterization and confirmation of hybrids derived from diverse CMS sources in sunflower (Helianthus annuus L.) - A C SHUBA,; R GURUMURTHY,; RAVI HUNJE, (Journal of Oilseeds Research, 2020)
The research was conducted at University of Agricultural Sciences, Dharwad, during 2016-2018 to evaluate hybrids derived from diverse CMS sources (CMS PET 1, CMS PEF and CMS-I ). Among the hybrids evaluated, FMS852A× RHA6D1 recorded 98% fertility restoration with on par performance of seed yield per plant (63.17 g/plant), oil content (38.48 %) and linoleic acid (65.69 %) with the check KBSH53.The parental lines and hybrids were characterized according to PPV&FRA guidelines The hybrids were confirmed by ORS312, ORS484, ORS460, ORS3640, ORS934, HA4011, ORS1065, ORS349, ORS309 and ORS316 SSR markers.